Saving creation nature and faith in the life of Holmes Rolston III - Preston, Christopher J. (Christopher James), 1968-; ebrary, Inc. (San Antonio : Trinity University Press, 2009)
Known as the "father of environmental ethics," Rolston is celebrated for his advocacy to protect the Earth's biodiversity and for his critical work reconciling evolutionary biology and Christianity. --from publisher description.
Shenandoah Valley childhood -- Country schoolhouse to atomic physics lab -- Graduate school to rural pastorate -- Preacher and Appalachian naturalist -- Leaving the ministry -- Discovering philosophy -- Colorado breakthrough -- Valuing wild nature -- Ecology and aesthetics in Yellowstone -- Wilderness and the developing world -- Feeding people, saving nature -- Christianity and the struggle with evolution -- Cruciform nature.
Includes bibliographical references (p. 231-233) and index.
Electronic reproduction.
Keywords: Rolston, Holmes, -- 1932-; Rolston, Holmes, -- 1932- -- Religion; Rolston, Holmes, -- 1932- -- Philosophy; Environmentalists -- United States -- Biography; Naturalists -- United States -- Biography; Philosophers -- United States -- Biography; Environmental ethics; Religion and science; Nature -- Religious aspects; Electronic books